2015
DOI: 10.1037/a0039216
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of Chinese Christians’ church attendance and religious steadfastness: A three-wave prospective study.

Abstract: who provided very useful and supportive comments on our earlier submissions. Sing-hang Cheung and Doris Mok made valuable suggestions at the early phase of this research. Heidi Chiu and Tina Lau assisted in library research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…A recent study (Hui et al, 2015) on values and faith steadfastness should be mentioned here. It found that hedonism and power values were predictive of unstable church attendance a year later, and that power, self-direction, and stimulation values were predictive of Christians exiting their faith a year later.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Hui et al, 2015) on values and faith steadfastness should be mentioned here. It found that hedonism and power values were predictive of unstable church attendance a year later, and that power, self-direction, and stimulation values were predictive of Christians exiting their faith a year later.…”
Section: Discussionmentioning
confidence: 99%
“…Values are another set of potential predictors that are taken into consideration. Schwartz's (Bilsky et al, 2011) Portrait Values Questionnaire (PVQ) has been included in studies about deconverts (Hui et al, 2018;Hui et al, 2015;Saroglou et al, 2020). From their longitudinal research with Chinese deconverts, Hui et al (2018;2015) conclude that "faith exit is predicted by the values of self-direction, stimulation, hedonism, achievement, and power."…”
Section: Introductionmentioning
confidence: 99%
“…Schwartz's (Bilsky et al, 2011) Portrait Values Questionnaire (PVQ) has been included in studies about deconverts (Hui et al, 2018;Hui et al, 2015;Saroglou et al, 2020). From their longitudinal research with Chinese deconverts, Hui et al (2018;2015) conclude that "faith exit is predicted by the values of self-direction, stimulation, hedonism, achievement, and power." Correspondingly, Saroglou et al (2020) report that deconverts have lower scores on conservation values such as security, conformity, tradition.…”
Section: Introductionmentioning
confidence: 99%
“…Hui et al (2015) conducted a longitudinal study looking into Hong Kong Chinese Christians’ church attendance and religious steadfastness. They used a three-wave approach to look at the churched versus the unchurched; church attendees versus church exit; and religious steadfastness versus church exit.…”
Section: The Hong Kong Contextmentioning
confidence: 99%
“…There are a few surprises in the findings with relevance to this research. First, those attending larger churches were found to have higher “stickability” with church and were less likely to exit the faith; second, full-time university students had a greater chance of losing their faith as they find other things to occupy their lives (Hui et al, 2015). These help us to better understand the complex factors and circumstances Hong Kong millennials Christians are facing in this fast-changing city today.…”
Section: The Hong Kong Contextmentioning
confidence: 99%